HHV-6A Infection of Papillary Thyroid Cancer Cells Induces Several Effects Related to Cancer Progression - Stefania Mardente; Maria Anele Romeo; Angela Asquino; Agnese Po; Maria Saveria Gilardini Montani; Mara Cirone (Viruses, 2023)
Recent studies have shown that thyrocytes are permissive to HHV-6A infection and that the virus may contribute to the pathogenesis of autoimmune thyroiditis. Thyroid autoimmune diseases increase the risk of papillary cancer, which is not surprising considering that chronic inflammation activates pathways that are also pro-oncogenic. Moreover, in this condition, cell proliferation is stimulated as an attempt to repair tissue damage caused by the inflammatory process. Interestingly, it has been reported that the well-differentiated papillary thyroid carcinoma (PTC), the less aggressive form of thyroid tumor, may progress to the more aggressive follicular thyroid carcinoma (FTC) and eventually to the anaplastic thyroid carcinoma (ATC), and that to such progression contributes the presence of an inflammatory/immune suppressive tumor microenvironment. In this study, we investigated whether papillary tumor cells (BCPAP) could be infected by human herpes virus-6A (HHV-6A), and if viral infection could induce effects related to cancer progression. We found that the virus dysregulated the expression of several microRNAs, such as miR-155, miR-9, and the miR-221/222 cluster, which are involved in different steps of carcinogenesis, and increased the secretion of pro-inflammatory cytokines, particularly IL-6, which may also sustain thyroid tumor cell growth and promote cancer progression. Genomic instability and the expression of PTEN, reported to act as an oncogene in mutp53-carrying cells such as BCPAP, also increased following HHV-6A-infection. These findings suggest that a ubiquitous herpesvirus such as HHV-6A, which displays a marked tropism for thyrocytes, could be involved in the progression of PTC towards more aggressive forms of thyroid tumor.